That girl from nowhere - Koomson, Dorothy (Century, 2015)
'Where are you coming from with that accent of yours?' he asks. 'Nowhere, ' I reply. 'I'm from nowhere.' 'Everyone's from somewhere, ' he says. 'Not me, ' I reply silently. Clemency Smittson was adopted as a baby and the only connection she has to her birth mother is a cardboard box hand-decorated with butterflies. Now an adult, Clem decides to make a drastic life change and move to Brighton, where she was born. Clem has no idea that while there she'll meet someone who knows all about her butterfly box and what happened to her birth parents. As the tangled truths about her adoption and childhood start to unravel, a series of shocking events cause Clem to reassess whether the price of having contact with her birth family could be too high to pay...